Postactivation performance enhancement (PAPE) using a vertical jump to improve vertical jump performance - Brink, N. J.; Constantinou, D.; Torres, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Postactivation performance enhancement (PAPE) is a principle that suggests that an acute bout of high intensity voluntary exercise will be followed by an improvement in strength, power, and speed of a subsequent task. This study intended to demonstrate how a maximal vertical jump (VJ) can enhance the outcome of a subsequent VJ compared to a multiple jump series (MJ) and a control. METHODS: In a randomized controlled, double blind trial, adult professional soccer players (N.=69) undertook maximal VJs at baseline and at 2 and 6 minutes postintervention after 1 of 3 interventions; 2 repetitions of a maximal VJ, 40 repetitions of a MJ or a walking control (CON). RESULTS: All baseline outcomes were similar between all the groups. Relative to the baseline there was a significant improvement for VJ in jump height and power output at 2 minutes of 1.89cm and 114.45W and relative to the baseline, MJ also had a significant improvement at 2 minutes of 1.51cm and 91.60W. By 6 minutes both groups had reverted to baseline values. There was no change in CON across the experiment and no significant difference between CON and the interventions. CONCLUSIONS: These findings suggest that 2 maximal VJs may enhance the outcome of a subsequent maximal VJ after 2 minutes and as much as a series of 40 jumps. However, these enhancements were not sustained for a further 4 minutes in either group.